Extracellular Matrix Biomarker, Fibulin-1, Is Closely Related to NT-proBNP and Soluble Urokinase Plasminogen Activator Receptor in Patients with Aortic Valve Stenosis (The SEAS Study) - Kruger, Ruan (Public Library of Science, 2014)
BACKGROUND: Fibulin-1, a circulating extracellular matrix glycoprotein, has been associated with arterial disease and elevated N-terminal prohormone B-type natriuretic peptide (NT-proBNP) in diabetes. Soluble urokinase plasminogen activator receptor (suPAR), a marker of inflammation, has been associated with subclinical atherosclerosis. Therefore, we aimed to explore the interplay between these biomarkers and mild to moderate aortic valve stenosis (AS). METHODS: In 374 patients with mild to moderate AS, we investigated the relationship of fibulin-1 with NT-proBNP, levels of suPAR and the degree of AS at baseline and after one and four years of treatment with Simvastatin 40 mg and Ezetimibe 10 mg or placebo. RESULTS: During treatment, fibulin-1 became more closely associated with NT-proBNP (β(year0) = 0.10, p = 0.08, β(year1) = 0.16, p = 0.005, β(year4) = 0.22, p<0.001) and suPAR (β(year0) = 0.05, p = 0.34, β(year1) = 0.16, p = 0.006, β(year4) = 0.13, p = 0.03) at the expense of the association to aortic valve area index (AVAI) (β(year0) = −0.14, p = 0.005, β(year1) = −0.08, p = 0.11, β(year4) = −0.06, p = 0.22) independently of age, gender, creatinine, and serum aspartate aminotransferase (Adj.R(year0) (2) = 0.19, Adj.R(year1) (2) = 0.22, Adj.R(year4) (2) = 0.27). Fibulin-1 was unrelated to aortic regurgitation, left ventricular mass, and ejection fraction. In patients with baseline AVAI<0.58 cm(2)/m(2) (median value), fibulin-1 was more closely associated to NT-proBNP (β(year0) = 0.25, β(year1) = 0.21, β(year4) = 0.22, all p<0.01), and suPAR (β(year0) = 0.09, p = 0.26, β(year1) = 0.23, β(year4) = 0.21, both p<0.01) independently of age, gender, AST and treatment allocation. CONCLUSIONS: Increased levels of fibulin-1 were independently associated with higher levels of suPAR and NT-proBNP especially in patients with lower AVAI, suggesting that fibulin-1 may be an early marker of AS as well as cardiac fibrosis secondarily to elevated left ventricular hemodynamic load.